Rates of acquisition and clearance of pneumococcal serotypes in the nasopharynges of children in Kilifi District, Kenya. - Abdullahi, O; Karani, A; Tigoi, C; Mugo, D; Kungu, S; Wanjiru, E; Jomo, J; Musyimi, R; Lipsitch, M; Scott, J (2012)
BACKGROUND: To understand and model the impact of pneumococcal conjugate vaccines at the population level, we need to know the transmission dynamics of individual pneumococcal serotypes. We estimated serotype-specific clearance and acquisition rates of nasopharyngeal colonization among Kenyan children. METHODS: Children aged 3-59 months who were identified as carriers in a cross-sectional survey were followed-up approximately 1, 2, 4, 8, 16, and 32 days later and monthly thereafter until culture of 2 consecutive swabs yielded an alternative serotype or no pneumococcus. Serotype-specific clearance rates were estimated by exponential regression of interval-censored carriage durations. Duration was estimated as the reciprocal of the clearance rate, and acquisition rates were estimated on the basis of prevalence and duration, assuming an equilibrium state. RESULTS: Of 2840 children sampled between October 2006 and December 2008, 1868 were carriers. The clearance rate was 0.032 episodes/day (95% confidence interval [CI], .030-.034), for a carriage duration of 31.3 days, and the rate varied by serotype (P< .0005). Carriage durations for the 28 serotypes with ≥ 10 carriers ranged from 6.7 to 50 days. Clearance rates increased with year of age, adjusted for serotype (hazard ratio, 1.21; 95% CI, 1.15-1.27). The acquisition rate was 0.061 episodes/day (95% CI, .055-.067), which did not vary with age. Serotype-specific acquisition rates varied from 0.0002 to 0.0022 episodes/day. Serotype-specific acquisition rates correlated with prevalence (r=0.91; P< .00005) and with acquisition rates measured in a separate study involving 1404 newborns in Kilifi (r=0.87; P< .00005). CONCLUSIONS: The large sample size and short swabbing intervals provide a precise description of the prevalence, duration, and acquisition of carriage of 28 pneumococcal serotypes. In Kilifi, young children experience approximately 8 episodes of carriage per year. The declining prevalence with age is attributable to increasing clearance rates.